BUILDING AN INFORMATION SYSTEM TO SUPPORT SCIENTIFIC AND EDUCATIONAL ACTIVITIES BASED ON THE ONTOLOGICAL MODEL OF THE SUBJECT AREA - Sadirmekova, Zh.B.; Sambetbayeva, M.A.; Tussupov, J.A.; Altynbekova, Zh.T. (Academic Scientific Journal of Computer Science, 2020)
The paper considers an approach to the creating an information system for supporting scientific and educational activities (ISSEA). Such a system is designed to systematize knowledge and information resources on the required educational and scientific topics, ensure their integration into a single information space and provide meaningful access to them. The conceptual approach to the development process of ISSEA is based on combining the most important components of Semantic Web technology, in particular, the use of ontology to represent the semantics of information educational resources and support their intellectual analysis and knowledge management methods to improve the effectiveness of access to heterogeneous loosely connected information on various aspects of educational and scientific activities. Such information systems (is) represent information objects of knowledge (in the form of a network of knowledge and data), search for them, and ontology-driven navigation. ISSEA is equipped with an ergonomic web user interface and special editors designed to manage the knowledge integrated into it.